Scientific and practical approaches and principles of guaranteed providing the population of Ukraine with drugs, veterinary medicines, medical and pharmaceutical services from the noopharmaceutical, nooethical and anti-aging perspectives - G. V. Zagoriy; I. V. Bushueva; M. S. Ponomarenko; Yu. M. Grigoruk (Zaporožskij Medicinskij Žurnal)
The article presents theoretical and practical substantiation of the basic methodological principles of strategy and tactics on the harmonization efforts, intentions and balanced interaction in the provision of guaranteed pharmaceutical and medical services on drugs and veterinary preparations sale to the population of Ukraine.